Pemberdayaan Petani Mengembangkan Diversifikasi Cabai dan Kompos Jerami Berbasis Zero Waste di Desa Padang Mutung - Ardian; Syafrinal Syafrinal; Nurbaiti Nurbaiti; Sispa Pebrian; Nursiani Lubis; Nur Suhada (Institut Pertanian Bogor, 2024)
The need for chillies in Riau Province continues to increase along with the increase in population. The price of chillies in Riau is very dependent on supply; if it decreases, it causes the price of chillies to rise; this condition is an opportunity for chilli farmers in Riau to plant or agribusiness chillies. It is hoped that Padang Mutung Village, Kampar Riau Regency, can become a centre for chilli production because of the potential for rice fields, and most of the population's livelihood is farming. One component of chilli production costs is inorganic fertilizer, which tends to be expensive, so production costs increase. Continuous application of inorganic fertilizer can reduce soil fertility. This community service activity aims to increase farmers' understanding of the need for diversification by optimizing the use of paddy fields and fields by planting chillies, increasing farmers' understanding of zero waste-based straw compost-making techniques, which can then be used as a substitute for the use of inorganic fertilizers. The methods used are lectures, discussions and field practice. The activity results showed that after participating in the outreach and practical activities, participants gained knowledge, understood and were able to make rice straw compost and chilli seedlings. Participants will gain knowledge and understand the importance of diversifying the cultivation of chillies apart from rice to optimize the use of paddy fields, yards and idle land. Participants can also learn how to make straw compost and use it to grow fibre chillies, understanding that there is an opportunity to do chilli agribusiness to overcome the chilli shortage. It is hoped that the people of Padang Mutung Village will have increased awareness regarding crop diversification techniques for making straw compost as an alternative to reducing inorganic fertilizers, which will likely increase efficiency in chilli cultivation.